Sub-lethal fungicide concentrations both reduce and stimulate the growth rate of non-target soil fungi from a natural grassland - dela Cruz, Jeane A.; Camenzind, Tessa; Rillig, Matthias C. (Frontiers in Environmental Science, 2022)
Conventional agriculture has relied extensively on the use of fungicides to prevent or control crop diseases. However, some fungicides, particularly broad-spectrum fungicides, not only eliminate target pathogens but also non-target and beneficial soil microbes due to the chemicals reaching the soil. This scenario is not only limited to agricultural soil, but this may also potentially occur when neighboring environments are contaminated by fungicides through spray drift. Although concentrations may be sub-lethal, the chemicals may accumulate in the soil when used continuously resulting in more toxic effects. In this study, the effect on the colony extension rate of 31 filamentous soil saprobic fungi, initially isolated from a protected grassland ecosystem, were analyzed under fungicide treatment. These isolates were considered naive (no prior exposure), hence presumed to have not developed resistance. Two currently used fungicides with different modes of action were added to Potato Dextrose Agar at varying concentrations. Results showed a wide range of tolerance and sensitivity to isopyrazam and prothioconazole. Fungi belonging to the phylum Basidiomycota were most negatively affected by both fungicides. Phylum Mucoromycota were the most tolerant to prothioconazole while isolates belonging to phylum Ascomycota differed in their responses to both fungicides. Negative effects on the growth rate were more pronounced at higher concentrations except for a few isolates that were inhibited at 1 mg L-1. A slightly positive effect was also observed in three of the isolates under fungicide treatment. Lastly, the negative impact of fungicides was not associated with the growth strategy of the fungi, whether fast growing or slow growing, rather it is isolate-specific and phylogenetically conserved. The results of this study demonstrate that co-occurring fungi differ in their sensitivity to fungicides even without prior exposure. This difference in sensitivity among co-occurring fungi may result in shifts in community composition of the soil fungal community to the detriment of the more sensitive isolates.